Muslim Consumers’ Food Safety Behaviour and Religious Commitment: An Empirical Study in the UAE Context - AL BAYARI, JEHAD RAFFEQ (2023)
As the final stage of the food chain, consumers’ food safety behaviour plays a major role in national food safety management systems. The knowledge, attitudes and practices (KAP) model, and application of traditional interventions have not ensured effective consumer food safety behaviour. Consumer behaviour is complex but is essential in managing national food safety systems; therefore, it is important to consider other factors that are important in the local cultural context, such as religious commitment. However, the impact of religious commitment on consumer food safety behaviour has not been investigated. In the United Arab Emirates (UAE), combining the effect of collectivism (e.g., subjective norms), religious commitment and consumer awareness with the KAP model may help to explain Muslim consumers’ food safety behaviour. This study examined the roles of consumer awareness and religious commitment in the relationships between food safety knowledge, attitudes, subjective norms and Muslim consumers’ food safety behaviour in the UAE. In addition, factors that impacted consumer food safety behaviour, particularly those influencing the relationships between food safety knowledge and attitudes and consumer food safety behaviour were explored. This thesis adopted a positivist philosophy and used a deductive, cross-sectional approach guided by the theory of planned behaviour and attachment theory to investigate the impact of the studied factors on consumer behaviour. A conceptual model was developed that incorporated 20 hypotheses. Quantitative data were collected from 1089 Muslim consumers in the UAE using a self-administered questionnaire. The collected data were analysed using the PLS-SEM software package. Empirical evidence from this research indicated that consumer awareness and religious commitment acted as a multiple mediator in the relationships between food safety knowledge, food safety attitudes, subjective norms and consumer food safety behaviour. Religious commitment also affected Muslim consumers’ food safety behaviour. This study demonstrated that an important factor influencing Muslim consumers’ food safety behaviour was Sharia and its teachings, as religious commitment emerged as a new construct related to food safety behaviour. This research contributed to building understanding of managing food safety in Muslim societies by offering new and deep insights of Muslim consumers’ behaviour, including subjective norms and religious commitment, which are highly relevant in Muslim society. The conceptual model developed in this thesis built on and improved existing models of food safety management by introducing attachment theory to currently used behavioural theories. The model may also inform a new and innovative guideline that considers religious commitment and behaviour-based food safety awareness. Regulatory and food safety authorities and other stakeholders can benefit from this model as it may assist in establishing a positive food safety culture, thereby promoting good food safety behaviours and reducing the incidence of foodborne illnesses. This research succeeded in explaining Muslim consumers’ food safety behaviour and concluded that Muslim consumers with greater religious commitment were more likely to demonstrate good food safety behaviour.